2002
DOI: 10.1016/s0893-133x(01)00428-6
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Neuroanatomy of Tourette's Syndrome An FDG PET Study III: Functional Coupling of Regional Cerebral Metabolic Rates

Abstract: Tourette's Syndrome (TS) is a poorly understood neurological disorder characterized by multiple motor and phonic tics and associated behavioral disturbances. While TS is clearly a disorder of motor function, the nature of the tics and the associated cognitive and behavioral features suggest that the pathogenesis extends beyond the motor domain. The motivational tension that commonly precedes motor and vocal tics and the sense of relief that follows their expression, as well as the irritability, impulsivity, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 31 publications
2
63
0
Order By: Relevance
“…The genetic underpinnings of the disorders remain unclear, although multiple traits of evidence suggest involvement of dopaminergic neurotransmission and abnormalities involving cortical-striatalthalamic-cortical circuitry [Jeffries et al, 2002;Ercan-Sencick et al, 2010]. The large genetic contribution to TS is well established and a few genes were reported to be responsible for monogenic subtype of TS [Rivi ere et al, 2009;Dehning et al, 2010].…”
Section: Discussionmentioning
confidence: 99%
“…The genetic underpinnings of the disorders remain unclear, although multiple traits of evidence suggest involvement of dopaminergic neurotransmission and abnormalities involving cortical-striatalthalamic-cortical circuitry [Jeffries et al, 2002;Ercan-Sencick et al, 2010]. The large genetic contribution to TS is well established and a few genes were reported to be responsible for monogenic subtype of TS [Rivi ere et al, 2009;Dehning et al, 2010].…”
Section: Discussionmentioning
confidence: 99%
“…Investigators have also examined how coupling between brain regions may be disturbed in TD. An fluorodeoxyglucose (FDG)-PET study reported differences in connectivity in TD patients and controls, particularly to the ventral striatum, as well as a reversal in coupling between the limbic and motor CSTC loops ( Jeffries et al 2002). That is, the motor and limbic circuits tended to be negatively correlated in healthy subjects and positively correlated in TD patients.…”
Section: Structural and Functional Neuroimaging Studiesmentioning
confidence: 99%
“…For example, functional MRI studies have shown that during active tic suppression, the putamen, globus pallidus, and bilateral thalamus were activated [Peterson et al, 1998]. Several other neuroimaging studies have also shown involvement of both caudate and lentiform nuclei (striatum) in TS [Jeffries et al, 2002;Ludolph et al, 2006;Peterson et al, 2001Peterson et al, , 2003]. However, no study has convincingly demonstrated direct involvement of white matter pathways linking the striatum with cortical regions in this disorder.…”
Section: Neuroimaging Findingsmentioning
confidence: 99%
“…However, several studies have more specifically suggested involvement of dorsal cortical regions, and the caudate [Bohlhalter et al, 2006;Fahim et al, in press] while other studies have suggested involvement of ventral cortical surfaces and the putamen [Jeffries et al, 2002;Ludolph et al, 2006;Makki et al, 2008] or both [Peterson et al, 1998]. The corticostriatal projection fibers from dorsal cortical surfaces travel mostly through the medial SC white matter pathway.…”
Section: Neuroimaging Findingsmentioning
confidence: 99%
See 1 more Smart Citation